Implementasi Kecerdasan Buatan dalam Penetapan Hukum Islam: Peluang dan Tantangan - Aryanti, Yosi; Fitrah, Mustannir; Ridha, Arif; Hendrisab, Hendrisab; Roszi, Jurna Petri; Yusrial, Yusrial (El-Rusyd, 2025)
The rapid development of Artificial Intelligence (Artificial Intelligence/AI) The Industrial Revolution 4.0 has become a vital part of various sectors of life and has transformed many aspects, including the legal field. In this digital age, the use of AI in enforcing Islamic law is an exciting advancement. This study analyzes the potential application of artificial intelligence in the process of establishing Islamic law (istinbath al-ahkam), an area that typically uses traditional methods. The aim of this research is to explore the opportunities offered by AI technology in improving the efficiency and accuracy of the Islamic law-making process, as well as to evaluate the potential challenges arising from the integration of these technologies. This research involved a comprehensive literature analysis and a qualitative approach. It also compared traditional Islamic law-making methods with the potential application of AI to the process. Research reveals that AI holds significant potential in various aspects of Islamic law enforcement, such as analyzing large volumes of religious texts, identifying patterns and trends in historical fatwas, and supporting the decision-making of Islamic scholars. However, the research also highlights significant challenges, such as the complexity of contextual interpretation, ethical issues related to religious authority, and the need to integrate AI with traditional methods without compromising the fundamental principles of Islamic law. This research highlights the importance of a balanced and ethical approach to the application of AI technology within the framework of Islamic law.